Demystifying some possible limitations of CLIL (content and language integrated learning) in the EFL classroom - Livia Carolina Ravelo (Universidad de La Sabana, 2014)
As a result of globalization, the world is constantly changing, people are overwhelmed with information and English is the language that typically serves as lingua franca to learn new content. In recent years, as a direct response to these changes, CLIL (Content and Language Integrated Learning) may be considered the approach in charge of providing suitable answers despite its possible limitations. Innovations, changes, students´ needs, new resources, meaningful content and a communicative perspective are involved in CLIL, a profitable and valuable means to teaching English as a Foreign Language. The main purpose of this work is to encourage EFL teachers to implement this approach, in spite of its constraints. Now the challenge seems to be finding out how this approach will lead us towards the achievement our goal.   Keywords: CLIL drawbacks, CLIL implementation, EFL teaching contexts